Consumption and diffusion of oxygen during the thermoxidative ageing process of elastomers: Absorption und Diffusion von Sauerstoff während der thermooxidativen Alterung von Elastomeren. Issue 5 (12th May 2016) - Herzig, A.; Johlitz, M.; Lion, A.
Abstract : Thermoxidative ageing of elastomers is investigated by having a closer look on the consumption and diffusion of oxygen during the exposure to elevated temperatures. After the introduction of some basic theory an experimental set‐up is described, which enables the measurement of the oxygen amount being absorbed during weathering. Hence the oxygen consumption of natural rubber was detected at elevated temperatures and for varying exposure times. The correlation of changes in the mechanical properties and the oxygen consumption is analysed in order to get new awareness of oxidation affecting the mechanical behaviour. Influences of diffusion effects on the degradation are investigated by the use of micro X‐ray tomography, which detects minor changes in density generated by oxidation. Density profiles over the cross‐section of the samples are created, which illustrate the appearance of diffusion‐limiting oxidation. The results offer a closer look at the thermoxidative ageing of natural rubber and should help to get a better understanding of the degradation during ageing. Finally the findings may improve the life‐time prediction of elastomeric components by providing the basis for the development of advanced material models.